Improving MSME Performance Through Digital Marketing For Improving Company Products - Sandy Septiano Winas; Muhammad Iqbal Fasa; Is Susanto (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to uncover effective digital marketing strategies for baby clothing products and to demonstrate the efficiency of enhancing the performance of MSMEs (Micro, Small, and Medium Enterprises) through the use of digital marketing. The method used is qualitative, with data collection conducted through observations and interviews with relevant parties. Secondary data was obtained from books, journal articles, and other supporting literature. The findings reveal several important insights. First, according to MSME owners, performance improvement can be achieved by creating engaging and memorable content that captures customers' attention. Second, from the customers' perspective, digital marketing allows MSMEs to reduce costs and become strong competitors compared to those who do not utilize this strategy. Third, the general public states that MSMEs need to enhance their digital marketing efforts to introduce their product and company identities in today's digital era. Overall, this research emphasizes the importance of digital marketing for MSMEs, particularly in strengthening their market position. By implementing appropriate strategies, MSMEs can not only improve their business performance but also expand their market reach. This indicates that utilizing digital technology in marketing is a crucial step toward achieving success in an increasingly digital world. This research uses descriptive qualitative method. The power needed as a research knife is primary data that the author obtained by observing and interviewing parties related to this research. Secondary data was obtained from various books, journal articles, and other supporting literature. While the results of this study are: based on the opinion of MSME business